2010
DOI: 10.1007/bf03325278
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity among adults in Serbia: Results from the National Health Survey

Abstract: High prevalence of overweight and obesity is a significant public health problem among Serbian adults. Efforts are needed to effectively promote daily physical activity and healthy eating through progressive modifications in lifestyle and the creation of supportive environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
3
13
1
2
Order By: Relevance
“…In this study, 41.2% of women with T-score < -2.5 had BMI lower than 19 kg/m 2 . Totally 24.2% of all participants were underweight, which is rather high in comparison to the prevalence of underweight reported by Grujic et al for healthy adult females in Serbia (14). This confirms the fact that individuals with low BMI have higher susceptibility to osteoporotic disorders.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, 41.2% of women with T-score < -2.5 had BMI lower than 19 kg/m 2 . Totally 24.2% of all participants were underweight, which is rather high in comparison to the prevalence of underweight reported by Grujic et al for healthy adult females in Serbia (14). This confirms the fact that individuals with low BMI have higher susceptibility to osteoporotic disorders.…”
Section: Discussionsupporting
confidence: 68%
“…Poor nutrition and lack of appropriate physical activity are major cause of obesity. Serbian Republic and neighbouring countries are areas in which people always used to have a habit to eat a lot of food because they were dealing with agricultural and hard physical works [23]. The obtained results showed that the majority of examined adolescents are in the group of healthy weight.…”
Section: Resultsmentioning
confidence: 89%
“…At the age of 19 all the boys have normal weight, while in girls has above and below healthy weight. Girls in the late adolescent years, in addition to obesity, have a problem with underweight [23]. Pokrajac-Bulian and Ambrosi-Randić in their study concluded that the girls in Croatia with high scores on the internalization and awareness scales were the most dissatisfied with their bodies [24].…”
Section: Resultsmentioning
confidence: 97%
“…The prevalence of obesity has increased in Serbia and it is a significant public health problem among Serbian adults: 55.7% of adult population was overweight while 19.0% of examinees were obese [3]. Genetic predisposition to obesity has been reported as a major risk factor for individuals [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, its prevalence is in the range 10-25% in men and 10-30% in women [1,2]. The prevalence of obesity increased in Serbia and it became a significant public health problem among Serbian adults: 55.7% of adult population was overweight while 19.0% of examinees were obese [3]. Obesity is a disease defined as abnormal accumulation of body fat mass, which may arise as a result of increased energy intake, decreased energy expenditure or increased partitioning of nutrients into fat.…”
mentioning
confidence: 99%